Evaluation of the Immunosafety of Cucurbit[n]uril on Peripheral Blood Mononuclear Cells In Vitro - Ekaterina Pashkina; Alina Aktanova; Elena Blinova; Irina Mirzaeva; Ekaterina Kovalenko; Nadezhda Knauer; Aleksandr Ermakov; Vladimir Kozlov (Molecules, 2020)
Cucurbiturils (CB[n]s) are nanoscale macrocyclic compounds capable of encapsulating a molecule or part of a molecule by forming host–guest complexes. Integration of drugs with CB[n] is used for the following purposes: controlling clearance; protection of the drug from biodegradation; targeted delivery to specific organs, tissues, or cells; reduction of toxicity; and improving solubility. One of the major problems encountered in the application of new drug delivery systems is lack of knowledge of their biological properties. CB[n], unlike many other often toxic nanoparticles, has extremely low toxicity, even at high doses. However, many aspects of the biological actions of these nanoscale cavitands remain unclear, including the immunotropic properties. In this study, we investigated the immunotoxicity and immunomodulation properties of CB[n]. It was found that CB[7] and CB[6] did not decrease the viability of mononuclear cells at all tested concentrations from 0.1–1 mM. Overall, the results indicated an immunomodulatory effect of different concentrations of CB[n]. In the case of a longer cultivation time, CB[n] had an immunostimulating effect, which was indicated by an enhancement of the proliferative activity of cells and increased expression of HLA-DR on lymphocytes.